(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Cardiovascular diseases are the leading causes of death globally resulting in 17-19 million death every year. The search for an effective medicine to manage cardiovascular disorder without any side effect has led to the use of traditional based medicine. 75% of the world’s population has been reported to depend on traditional medicine as their basic form of health care and this has resulted to the use of herbal medicine in the treatment and management of metabolic diseases. The study evaluated the effect of methanolic extract of Ricinus communis on DDVP-induced cardiotoxicity in male Wistar rats. Thirty-two (32) male Wistar rats were randomly divided into four groups of eight (8) rats each. Group A served as control rats, received 10mL/Kg of dimethyl sulfoxide (DMSO) and distilled water solution (vehicle) for six weeks. Group B served as DDVP-induced rats and were exposed to DDVP (15 minutes daily) for 3 weeks without any treatment. Group C rats received DDVP as in group B and then administered 300mg/kg of R. communis extract for 42days. While Group D rats were administered 300mg/kg of R. communis extract daily, for 6 weeks in addition to normal feed and water. Exposure to DDVP caused significant cardiac dysfunction evidence by alteration in cardiovascular variables and electrocardiac function, compromised lipid profile and reduced antioxidant enzymes. However, treatment with methanolic extract of Ricinus communis improved antioxidant defense system, attenuate hemodynamic impairment and left ventricular dysfunction, as well as inhibit lipid peroxidation and prevent hyperlipidemia in rats. In addition, histopathology observation showed that Ricinus communis extract was able to regenerate the myocardial injury caused by exposure to dichlorvos. In conclusion, Ricinus communis exhibited cardioprotective properties and may be a potential remedy for cardiovascular diseases with low risk of toxicity